Through Literacy to Fluency: Reading in the Religious Studies Classroom - Medine, Carolyn M. Jones (Teaching theology and religion, 2016)
This paper addresses a perennial question of the religious studies and, indeed, of most liberal arts classrooms: How do I get my students to read texts thoroughly and with understanding? After briefly reviewing the National Assessment of Adult Literacy (NAAL) data, I argue that what teachers desire is not just basic literacy, but fluency, which is the capacity to read analytically (and, for me, appreciatively), deploying the strategies of reading in a high process, improvisational mode. I unpack the elements and efficacy of one close reading classroom teaching practice I use, guided annotation, as a strategy for developing fluency. I argue that close analysis of a short, intentionally chosen passage with a guiding question builds towards reading fluency. Annotating short passages, singly and then in relation to other passages, with the author's and disciplinary concerns as the foci, practices the skills that build fluency. Annotation is akin to playing scales in music, repeating a baseline task of reading; working slowly and simply at first, but then with increasing speed and complexity, moving the student towards reading whole texts well.